De Novo assembly, characterization and development of EST-SSRs from Bletilla striata transcriptomes profiled throughout the whole growing period - Xu, Delin (PLoS One, 2018)
Bletilla striata is an endangered orchid that has been used for millennia as a medicinal herb, in cosmetics and as a horticultural plant. To construct the first nucleotide database for this species and to develop abundant EST-SSR markers for facilitating further studies, various tissues and organs of plants in the main developmental stages were harvested for mRNA isolation and subsequent RNA sequencing. A total of 106,054,784 clean reads were generated by using Illumina paired-end sequencing technology. The reads were assembled into 127,261 unigenes by the Trinity package; the unigenes had an average length of 612 bp and an N50 of 957 bp. Of these unigenes, 67,494 (51.86%) were annotated in a series of databases. Of these annotated unigenes, 41,818 and 24,615 were assigned to gene ontology categories and clusters of orthologous groups, respectively. Additionally, 20,764 (15.96%) unigenes were mapped onto 275 pathways using the KEGG database. In addition, 25,935 high-quality EST-SSR primer pairs were developed from the 15,433 unigenes by MISA mining. To validate the accuracy of the newly designed markers, 87 of 100 randomly selected primers were effectively amplified; 63 of those yielded PCR products of the expected size, and 25 yielded products with significant amounts of polymorphism among the 4 landraces. Furthermore, the transferability test of the 25 polymorphic markers was performed in 6 individuals of two closely related genus Phalaenopsis and dendrobium. Which results showed a total of 5 markers can successfully amplified among these populations. This research provides a comprehensive nucleotide database and lays a solid foundation for functional gene mining and genomic research in B. striata. The developed EST-SSR primers could facilitate phylogenetic studies and breeding.